Trade unions of the world (Gale virtual reference library, 2005)
This comprehensive resource covers trade unions in every independent country in the world. Entries feature detailed coverage of key unions; details of trade union centers, including contact information, Web site URLs, international affiliations and more; discussion of the political and economic backgrounds against which the unions operate; an overview of trade unionism; and more.